2021
DOI: 10.1177/08982643211020996
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of the BAILAMOSTM Dance Program on Physical Activity Levels and Cognition of Older Latino Adults: A Pilot Study

Abstract: Objective: To investigate the effects of the BAILAMOSTM dance program on physical activity (PA), cardiorespiratory, and cognitive health. Methods: A parallel, two-armed pilot study was conducted with 57 older Latinos randomized to the BAILAMOSTM dance program ( n = 28) or health education (HE) ( n = 29). We conducted two- and three-way repeated-measures ANOVAs. Results: BAILAMOSTM participants increased participation in leisure moderate-to-vigorous PA (LMVPA) ( F[1,53] = 3.17, p = .048, η2 G = .01) and perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
55
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(55 citation statements)
references
References 77 publications
0
55
0
Order By: Relevance
“…Considering the inclusion and exclusion criteria, a total of nine studies were included in this review, assessing the effect of seven interventions [ 9 , 15 , 34 , 35 , 36 , 37 , 38 , 39 , 40 ]. Figure 1 shows the flow chart of the study selection process.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Considering the inclusion and exclusion criteria, a total of nine studies were included in this review, assessing the effect of seven interventions [ 9 , 15 , 34 , 35 , 36 , 37 , 38 , 39 , 40 ]. Figure 1 shows the flow chart of the study selection process.…”
Section: Resultsmentioning
confidence: 99%
“…All studies except one were conducted in the US; the Centre of Social Health Services for Older Adults (COASH) program was conducted in Mexico [ 34 ]. Five of the studies were randomized controlled trials (RCT) or cluster-RCT (Let’s Walk!, Worth the Walk, Community of Voices (COV), BAILAMOS TM , and BAILA) [ 36 , 37 , 38 , 39 , 40 ]. Three studies had a pre-post quasi-experimental design (COASH, Abuelas en Acción (AEA), and Healthy Living Wellness Program (HLWP)) [ 9 , 15 , 34 , 35 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Dance coordinates the neurosensory and musculoskeletal systems to execute rhythmic movements (de Natale et al, 2017). A recent study on a 16 week BAILAMOS dance program in the United States reported the program's positive impact on the physical activity levels and cognition of older Latino adults (Balbim et al, 2022; Marquez et al, 2022). Dance improves the muscle strength and flexibility of the upper and lower limbs, as well as the coordination of movements (Douka et al, 2019).…”
Section: Introductionmentioning
confidence: 99%